Magnetic Attachment as Retained for Mandibular Overdenture : A Case Report - Sutiyo, Sutiyo; Sudarman, Ian A; Thalib, Bahruddin; Ikbal, Muhammad; Syamsuddin, Rezki W (Journal of Case Reports in Dental Medicine, 2021)
Objective: Overdenture is a denture design that can be made in partial or complete loss of teeth , that has support from teeth and natural tooth roots that are still strong and healthy, and already received adequate endodontic treatment. If the tooth is extracted, the process of alveolar bone resorption will follow and worsen the retention and stability of the denture. One alternative in making complete dentures by retaining the remaining teeth in certain conditions is using an overdenture Methods: A 41 year old female, came to the Dental Hospital of UNHAS with a chief complaint of difficulty in eating and lack of confidence. Clinical examination shown a complete edentulous in the upper jaw and partial edentulous in the lower jaw. The remaining teeth were 33, 34 and 43. Magnetic Attachments were planned on 33 and 43 and metal coping on 34 as retained for mandibular overdenture.Results: Treatment with an overdenture is a good consideration because it is considered to be able to retain teeth in the alveolar process, which will provide better denture support than conventional dentures.Conclusion: Magnetic attachments significantly increase the retention of mandibular overdenture, patient is more satisfied and comfortable. Patient doesn’t experience difficulties in insert and removing the denture because when the denture is slightly shifted, the magnetic attachment returns it to its original position.